SEBUAH KESAN AKAN KEHENINGAN BUNYI - Dreeartika Adi J.W (SELONDING, 2013)
An Impression of the Silence of Sounds is the title of a musical composition that put emphasis on the silence in either a sensible or insensible reality. The phenomenon of sounds as both real and not-real is attempted to be expressed through this composition, after going through the stages of scientific study of acoustics (as represented in symbols) and imagination. This composition was inspired by the works of musical composition and natural phenomena that are identical to silence itself. This musical work was realized, first, through some processes or methods, such as initial stimulation, ideation, exploration, improvisation, and formation that ended up in presentation. The composition intends to integrate two musical media; of Western and Eastern (Gamelans). Moreover, it encompassing all three movements; adagio, allegro, and returns to the beginning of the adagio section. In its own context, the composition represents an affirmation of the existence of sounds in a silence as has been demonstrated in natural science disciplines. Further, it attempts to criticize public perception that the beauty of art is solely a sensual pleasure. Keywords: Impression, Silence, Sounds, acoustics, imagination.